Evaluation of grain characteristics of domestic wheat (Triticum aestivum L.) obsolete cultivars and landraces - Kondić, Danijela; Oručević Žuljević, Sanja; Hajder, Đurađ; Selimbegović, Enez (Italian Journal of Agronomy, 2020)
The research on wheat accessions was carried out in order to evaluate their grain characteristics. Experiment was set in the agro-ecological conditions of Banja Luka in two experimental years (2015/16 and 2016/17). Ten obsolete wheat cultivars (Brkulja, Ličanka, Partizanka, Vuka, Talijanka, Šiđanka, Orašanka, Lozničanka, Dokučajevskaja and Nemcitaevskaja) and two landraces (Podrašnica and Previja) were used. Following grain characteristics were evaluated: grain length (mm), grain width (mm), grain thickness (mm), grain volume (mm3), grain surface area (mm2), thousand grain weight (g) and grain protein content (%). Significant interactions were found for most of these traits. The relationship between traits was established by correlation analysis. In this study genotypes Brkulja and Šiđanka showed promising for most of the grain characteristics, while Vuka and Partizanka obtained the highest grain protein content.